ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PRODUK MADU IBNU ASYIR DI ACEH - Yuliana, Ema; Ritonga, Ritonga; Konadi, Win; Nurmalawati, Nurmalawati (Fakultas Ekonomi Universitas Almuslim Bireuen, 2025)
The study measures the extent to which the impact of social media, product quality factors and service The problem of consumer loyalty by analyzing the factors that influence product purchasing decisions is still interesting to study. In quantitative descriptive research, it is limited to promotion factors, product quality and price. The research unit of Ibnu Asyir honey products in Aceh, with a path analysis approach. By conducting a survey of 96 regular consumers of the products studied. The results of the study obtained information that: (1) product purchasing decisions are directly and indirectly influenced by promotion factors of 13.96%, product quality factors of 38.38% and price factors of 23.59%. (2) Simultaneously, promotion, product quality and price influence the decision to purchase Ibnu Asyir Honey products in Aceh by 69,3%. (3) Between the three influencing factors, there is a causal relationship with a fairly close category.